2019
DOI: 10.1186/s12974-019-1439-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of inflammation and oxidative stress genes does not play a major role in the occurrence of adverse events of dopaminergic treatment in Parkinson’s disease

Abstract: Background Inflammation and oxidative stress are recognized as important contributors to Parkinson’s disease pathogenesis. As such, genetic variability in these pathways could have a role in susceptibility for the disease as well as in the treatment outcome. Dopaminergic treatment is effective in management of motor symptoms, but poses a risk for motor and non-motor adverse events. Our aim was to evaluate the impact of selected single-nucleotide polymorphisms in genes involved in inflammation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 77 publications
(93 reference statements)
1
31
0
Order By: Relevance
“…While previous studies have analyzed associations between the IL-10-1082 G/A (rs1800896) polymorphism with PD [2,12,13,17,34], none have been established with IL-10 -819 T/C (rs1800871) and IL-10 -592 C/A (rs1800872) polymorphisms [4,12,34,35]. In this metaanalysis, three additional studies [33,36,37] were included for the analysis of IL-10 -1082 G/A polymorphisms. Our analyses showed that the A allele (A vs. G, OR = 1.731; 95% CI 1.338-2.239, P = 0.000, I 2 = 0%, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While previous studies have analyzed associations between the IL-10-1082 G/A (rs1800896) polymorphism with PD [2,12,13,17,34], none have been established with IL-10 -819 T/C (rs1800871) and IL-10 -592 C/A (rs1800872) polymorphisms [4,12,34,35]. In this metaanalysis, three additional studies [33,36,37] were included for the analysis of IL-10 -1082 G/A polymorphisms. Our analyses showed that the A allele (A vs. G, OR = 1.731; 95% CI 1.338-2.239, P = 0.000, I 2 = 0%, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the effects of the polymorphism on drug actions were not absolutely consistent. For example, patients with SOD2 rs4880 T allele taking dopaminergic anti-parkinson drugs had less nausea and vomiting, but the motor adverse reactions remained unchanged (32). Further, clozapine response in patients with schizophrenia had not been affected with Val16Ala SOD2 polymorphism (33).…”
Section: Discussionmentioning
confidence: 97%
“…38 Buckman et al found that brain atrophy measured after head computerized tomography scans in patients with chronic SCZ was negatively correlated with GSH-px activity in platelets, which was more significant in patients with SCZ with negative symptoms as the core clinical manifestation. 39 Currently, a tremendous amount of domestic and foreign scientific research have proven that GPx-1 polymorphisms are associated with different diseases, such as coronary artery disease, 22 cancer, [40][41][42][43][44][45] diabetes and its vascular complications, 46 rheumatoid arthritis, 47 Huntington's disease, 48 PD, 26,49 autism, 50 and postpartum hemorrhage. 51 However, research into the involvement of GPx-1 in SCZ is lacking.…”
Section: Introductionmentioning
confidence: 99%